1992
DOI: 10.1002/tera.1420450208
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid‐induced spina bifida: A mouse model

Abstract: Prenatal exposure to the antiepileptic drug valproic acid (VPA) has been associated with the formation of spina bifida aperta, meningocele, and meningomyelocele in the human. Until now, a direct relationship between VPA application and spina bifida has not been experimentally demonstrated. VPA was known only to induce exencephaly in mice, a defect of the anterior neural tube. Maximal sensitivity toward production of this defect was on day 8 of gestation (plug day = day 0). The closure of the posterior neuropor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 22 publications
5
67
0
1
Order By: Relevance
“…The structural elements previously shown to be essential for teratogenicity have been confirmed by the results of the expression of NCAM and PST1: the molecule has to bear a carboxylic group, and the carbon atom adjacent to the carboxylic group has to have one hydrogen atom (Ehlers et al, 1992). In addition, the sp 3 configuration at carbon atom C-2 is essential, because analogs (E-2-en-VPA) in which carbon atom C-2 is sp 2 -hybridized were not active either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The structural elements previously shown to be essential for teratogenicity have been confirmed by the results of the expression of NCAM and PST1: the molecule has to bear a carboxylic group, and the carbon atom adjacent to the carboxylic group has to have one hydrogen atom (Ehlers et al, 1992). In addition, the sp 3 configuration at carbon atom C-2 is essential, because analogs (E-2-en-VPA) in which carbon atom C-2 is sp 2 -hybridized were not active either in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 68%
“…In the mouse, the predominant neural tube defect after single VPA injection on day 8 of gestation is exencephaly, an anterior neural tube defect. Repeated treatment on day 9 of gestation induces posterior neural tube defects (spina bifida aperta and occulta) (Ehlers et al, 1992). In the search for new drugs with selective anticonvulsant activities and less toxicity, numerous derivatives and various metabolites of VPA have been investigated and found to exert anticonvulsant activity in rodents (Nau et al, 1991;Ehlers et al, 1992).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…VPA treatment during early neural tube formation (E8 in the mouse) results in exencephaly, which is the rodent equivalent of human anencephaly. Others reported that spina bifida can be induced in some mouse strains when injected three times at 6-h intervals on E9 [Ehlers et al, 1992;Emmanouil-Nikoloussi et al, 2004;Finnell et al, 1988;Menegola et al, 1996]. Pharmacokinetic study showed that VPA can induce neural tube defects in exposed mouse embryos when this drug reaches maternal plasma concentrations of 225 μg/ml, irrespectively of the route of administration [Nau, 1985].…”
Section: Phenobarbital (Solfoton)mentioning
confidence: 99%